Art Therapy sebagai Intervensi Edukatif dalam Mengembangkan Ekspresi Emosi Anak Usia Dini - Lestari, Indah; Sucipto, Sucipto; Santoso, Santoso; Zamroni, Edris (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Emotional expression is a crucial aspect of early childhood development that needs to be nurtured appropriately. This community service activity aimed to help early childhood education (PAUD) students in Bae District, Kudus Regency, to develop their emotional expression through an art therapy approach. The method used in this activity was a participatory approach involving children, teachers, and parents in drawing and coloring sessions designed with therapeutic elements. The results indicated that children were more able to express their emotions through the artwork they created. Teachers and parents also observed positive changes in how children expressed their feelings and interacted with their surroundings. Therefore, art therapy can be an effective and enjoyable educational approach to support the emotional development of young children.